Synthesis of a Diamino Substituted Terphenyldivinyl Chromophore - Jun-Ru Wang; Ru Liu; Zhen-Ting Du; An-Pai Li (Molecules, 2009)
(E,E)-1,4-bis(4'-aminostyryl)-2,5-bis(octyloxy)-benzene (6) and its derivative (E,E)-1,4-bis(4'-acetamidostyryl)-2,5-bis(octyloxy)-benzene (7) were synthesized and characterized after alkylation, bromomethylation, Horner-Emmons reaction and reduction from hydroquinone. In order to gain more molecular electronic data, HOMO and LUMO of compound 6 have been calculated by Gaussian 03 W.